Path Apps for Box of Ramadhan - Ling, Teng Mee; Kasim, Shahreen; Saedudin, RD Rohmat (International Journal of Advanced Science Computing and Engineering, 2019)
Â destination of rural area due to unclear addresses. This problem alsofaced by owner and members of the Box of Ramadhan when theyneed to give delivery services to underprivileged people cause lowefficiency of service provided. Thus, this project is conducted todesign and develop an application called Path Apps for Box ofRamadhan for Android device user to solve problems of reachdestination and get related information to reduce overall timespending. Unified Modelling Language diagram used to show therelationship and interaction among all classes. The proposed systemis categories into two different interfaces as admin interface and userinterface. The application consists of few modules such as login andregistration, user list, profile, current location, route, multiplemarkers and address list and chat modules. Time management, routeplanning and inventory will be under control by user according toprogram schedule. This contribute to high efficiency of work.